Opportunities of hidden hydropower technologies towards the energy transition - Karapici, Valbona; Trojer, Alex; Lazarevikj, Marija; Pluskal, Tomáš; Chernobrova, Anna; Nezirić, Emir; Zuecco, Giulia; Alerci, Aldo Leonardo; Seydoux, Martin; Doujak, Eduard; Rudolf, Pavel (Elsevier BV, 2024)
Hydropower is the world's most exploited renewable energy source. It provides a substantial, flexible, and reliable source of renewable energy, complementing other renewables like solar and wind power. Besides conventional hydropower potentials and technologies, the development of technologies for the exploitation of hidden hydropower potentials is an ongoing process. This paper presents the current state of hidden hydropower technologies and links them with possible applications in different hydropower potentials. Technologies and potential applications are structured within three main groups (pressurized systems, hydro storage, unpressurized systems), with their mutual interconnections analysed and displayed throughout the paper. The opportunity for the application of hidden hydropower technologies in different roles within the energy system is recognized through the concepts of off- and on-grid roles, the prosumer concept, and on-site measurement powering. This paper shows that hidden hydropower technologies could emerge as significant contributors to a smoother energy transition, especially with the prosumer and off-grid concepts.
Keywords: Hydropower; Hidden hydropower; Hydropower technologies; Hydro storage; Pump as turbine; Prosumer; Energy Harvester